Less Nutrients but More Phytoplankton: Long-Term Ecosystem Dynamics of the Southern North Sea - Xu, Xu; Lemmen, Carsten; Wirtz, Kai W. (Frontiers in Marine Science, 2020)
We here assess long-term trends in marine primary producers in the southern North Sea (SNS) with respect to ongoing regional Earth system changes. We applied a coupled high-resolution (1.5–4.5 km) 3d-physical-biogeochemical regional Earth System model that includes an advanced phytoplankton growth model and benthic biogeochemistry to hindcast ecosystem dynamics in the period 1961–2012. We analyzed the simulation together with in situ observations. Coinciding with the decreasing nutrient level at the beginning of the 1990s, we find a surprising increase in phytoplankton in the German Bight, but not in the more offshore parts of the SNS. We explain these complex patterns by a series of factors which are lacking in many state-of-the-art coupled ecosystem models such as changed light availability and physiological acclimation in phytoplankton. We also show that many coastal time-series stations in the SNS are located in small patches where our model predicts an opposite trend than found for the surrounding waters. Together, these findings call for a reconsideration of current modeling and monitoring schemes.